Efficacy and tolerability of Glucantime versus Sodium Stibogluconate in Leishmaniasis from January 1999 to December 2001 in the C.S. San Camilo, Pozuzo – Oxapampa, Pasco - Belzusarri Padilla, Odórico Ivan (2022)
In a prospective study of patients with leishmaniasis diagnosed at the San Camilo of Pozuzo Health Center, we compared two treatments: glucantime 20 mg Base/kg/day IM for 20 days, with a maximum dose of 1275 mg/day (treatment performed from January 1999 to December 2000), versus sodium stibogluconate 20 mg Base/kg/day IM for 30 days, with a maximum dose of 1500 mg/day (treatment performed from January to December 2001). Of the 173 leishmaniasis patients, 116 had L. cutanea (67.05%) and 57 had L. cutaneomucosa (32.95%). Of the 135 patients treated with glucantime (78.03%) and 38 with sodium stibogluconate (21.96%), 45 (33.3%) and 25 (67.78%) respectively, presented adverse reactions. Six patients under treatment with glucantime (4.44%) and 4 treated with sodium stibogluconate (10.53%) discontinued treatment. Fifteen patients under glucantime (10 affected with L. Cutaneomucosa and 5 with L. Cutanea) and 2 patients with sodium stibogluconate (one with L. Cutaneomucosa and one with L. Cutanea) relapsed. Both pentavalent antimonial showed relative similar efficiency achieving complete healing of lesions and negative frotis in posterior con trols after treatment. Treatment with glucantime was best tolerated due to less adverse effects and fewer desertions.